View of Pre-Service Teacher Regarding Math and Science Literacy - Liana, Metta; Elvi, Mariyanti; Asma Riani Siregar, Nur; Susanti, ‎ (KnE Social Sciences, 2024)
As future teacher candidates, pre-service teachers must have good mathematical and scientific literacy. Therefore, this study aims to describe the prospective of teacher students’ mathematical literacy and scientific literacy. This type of research is a qualitative descriptive study with deep interview techniques. A total of 8 studentteacher candidates from the mathematics education, biology, and chemistry education study programs were selected to be interviewed. The results showed that students equipped with an understanding of mathematical literacy and scientific literacy in literacy-related programs and literacy lectures responded positively. Keywords: teacher regarding, math literacy, science literacy